Nociceptive and Histomorphometric Evaluation of Neural Mobilization in Experimental Injury of the Median Nerve - Marieli Araujo Rossoni Marcioli; Josinéia Gresele Coradini; Regina Inês Kunz; Lucinéia de Fátima Chasko Ribeiro; Rose Meire Costa Brancalhão; Gladson Ricardo Flor Bertolini (The Scientific World Journal)
The carpal tunnel syndrome is the most common peripheral neuropathy in the upper limb, but its treatment with conservative therapies such as neural mobilization (NM) is still controversial. The aim of this study was to investigate the efficacy of the NM as treatment in a model of median nerve compression. 18 Wistar rats were subjected to compression of the median nerve in the right elbow proximal region. Were randomly divided into G1 (untreated), G2 (NM for 1 minute), and G3 (NM for 3 minutes). For treatment, the animals were anesthetized and the right forelimb received mobilization adapted to humans, on alternated days, from the 3rd to the 13th day postoperatively (PO), totaling six days of therapy. Nociception was assessed by withdrawal threshold, and after euthanasia histomorphometric analysis of the median nerve was performed. The nociceptive evaluation showed in G2 and G3 delay in return to baseline. Histomorphometric analysis showed no significant differences in the variables analyzed. It is concluded that the NM was not effective in reducing nociceptive sensation and did not alter the course of nerve regeneration.